If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -1(3 + -1x) = 0 8x + (3 * -1 + -1x * -1) = 0 8x + (-3 + 1x) = 0 Reorder the terms: -3 + 8x + 1x = 0 Combine like terms: 8x + 1x = 9x -3 + 9x = 0 Solving -3 + 9x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 9x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 9x = 0 + 3 9x = 0 + 3 Combine like terms: 0 + 3 = 3 9x = 3 Divide each side by '9'. x = 0.3333333333 Simplifying x = 0.3333333333
| 3(2)x+1y=7 | | N(N-24)=-128 | | 9p-4=8p | | 2r(r-7)+8r=56 | | 3y-7=-13+y | | -8/3= | | 5(3+6x)-5=130 | | 7(9x+2)=63x-9 | | x+.20x=24 | | 5z-27=2z | | .17a+7=2 | | 44=4(2y+3) | | v^2=-2v+24 | | .5a+5=-4 | | z^3-7z^2+10z=0 | | .04x+.03(5000-x)=180 | | z=m^2-m(1-SQRT(-1))-3(2+SQRT(-1)) | | 2j=64 | | 2j=6473554256376468578575364262 | | factorisex^2-1-42=0 | | 5(d+15)=90 | | 0=x-11-2x | | 12x+10=12x-8 | | x^2-1-42=0 | | -4x-13x=136 | | 3z=-174 | | 8z+4z=48 | | 8s-5=-5+5s | | -7x-23=-163 | | -(-27)d=16.2 | | 4x-12=64+2x | | 184=4(9)(4)+2(4)H |